Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\left(2x+10\right)\left(x^2-9\right)=0\)
\(\Leftrightarrow\)\(2\left(x+5\right)\left(x^2-3x+3x-9\right)=0\)
\(\Leftrightarrow\)\(2\left(x+5\right)\left(x-3\right)\left(x+3\right)=0\)
\(\Leftrightarrow\)\(x+5=0\) \(\Leftrightarrow\)\(x=-5\)
hoặc \(x-3=0\) hoặc \(x=3\)
hoặc \(x+3=0\) hoặc \(x=-3\)
Vậy....
Dạng 3 :
a) 3x - 10 = 2x + 13
=> 3x - 2x = 13 - 10
=> x = 3
b) x + 12 = -5 - x
=> x + x = -5 - 12
=> 2x = -17
=> x = -8,5
c) x + 5 = 10 - x
=> x + x = 10 - 5
=> 2x = 5
=> x = 2,5
d) 6x + 23 = 2x - 12
=> 2x - 6x = 23 + 12
=> -4x = 35
=> x = -8,75
e) 12 - x = x + 1
=> x + x = 12 - 1
=> 2x = 11
=> x = 5,5
f) 14 + 4x = 3x + 20
=> 4x - 3x = 20 - 14
=> x = 6
1
a, 4x - 3x + 1 = 5
x =5-1
x =4
Vậy x=4
b, (2x - 4 ) . 3x =0
=> 2x - 4 =0 hoặc 3x = 0
=> 2x =4 hoặc x=0
=> x =2 hoặc x=0
vậy x= 2 hoặc x=0
c, x . ( x -1 ) - ( x-1 )=0
(x-1) . (x-1 ) =0
(x-1)2 =02
x-1 =0
x =1
vậy x=1
2/ a, 7 . (x - 1 ) = 6x + 3
7x -7 = 6x +3
7x - 6x =7+3
x =10
vậy x=10
b, 8 . ( 2x - 3 ) -15x =4
16x - 24 -15x =4
16x - 15x =4+24
x =28
vậy x=28
c, 7 . 10 + ( x-1 ) .2 =100
70 + 2x -2 =100
2x -2 =100-70
2x -2 =30
2x =30+2
2x =32
x =16
vậy x=16
chúc bn học tốt
đề câu c là sao bn
|x(x+1)| + |x(x-1)